Islamic cooperative: an alternative to commercial Islamic banking - Gonsalves, Richard Gerald; Kassim, Salina (IIUM, 2015)
The current Islamic banking model which is based on the concept of commercial banking has been criticised as too rigid and not conducive towards achieving the objectives of an Islamic economy. This paper aims to evaluate the suitability of the cooperative model as an alternative to the commercial banking model and to discern whether the values of cooperative would be more compatible to the ideals of Islam. We find that cooperative shares many of the social and economic values as are found in the teachings of Islam. When the essence of Islamic finance principles such as free from interest, transparency, and application of profit and loss sharing is combined with the values and principles of the cooperative model, what is created is an efficient, fast growing organisation with the potential to greatly benefit its members as well as the society in general.